Previous pregnancy loss and gestational cardiovascular health: A prospective cohort of nulliparous women - Ma, Shuang-shuang; Yin, Wan-jun; Wang, Peng; Wang, Hai-xia; Zhang, Lei; Jiang, Xiao-min; Zhang, Ying; Tao, Ruixue; Ge, Jin-fang; Zhu, Peng (Frontiers in Public Health, 2023)
Objectives To estimate the association of previous pregnancy loss with subsequent cardiovascular health during gestation and to examine the role of high-sensitivity C reactive protein (hs-CRP) in the association. Methods A total of 2,778 nulliparous pregnant women were recruited between March 2015 and November 2020 in Hefei city, China. Their cardiovascular health (CVH) including prepregnancy body mass index (BMI), blood pressure, total cholesterol, fasting plasma glucose, and smoke status were recorded at 24–28 weeks’ gestation, as well as their reproductive history. Multivariate linear and logistic regression were performed to examine the association of pregnancy loss with cardiovascular health. And the role of hs-CRP between pregnancy loss and CVH was assessed by the mediation analysis. Results Compared with women who have no pregnancy loss, women with a history of spontaneous or induced abortions had higher BMI (β, 0.72, 95% CI, 0.50 to 0.94) and fasting plasma glucose (β, 0.04, 95% CI, 0.01 to 0.07), and had lower total CVH scores after adjusting for confounders (β, −0.09, 95% CI, −0.18 to −0.01). CVH scores were most significantly decreased among women with 3 or more induced abortions (β, −0.26, 95% CI, −0.49, −0.02). The contribution of pregnancy loss to poorer gestational CVH mediated by increased hs-CRP levels was 23.17%. Conclusion Previous pregnancy loss was associated with poorer cardiovascular health during gestation, which may be mediated by their gestational inflammatory status. Exposure to miscarriage alone was not a significant predictor of poorer CVH.